Perubahan Kualitas Hidup DLQI Sebelum Dan Sesudah Penggunaan Krim Racikan Anti Jerawat Klinik Sukma - Angelina, Chesia; Tansil Tan, Sukmawati (Health Information : Jurnal Penelitian, 2023)
Acne vulgaris is a disease of the pilosebaceous unit characterized by open or closed comedones, papules, pustules, nodules and cysts. Acne is one of the most common diseases that are treated by dermatologists and occurs mostly in adolescents. Quality of life is a person's perception of his existence in life, in the context of his value system culture and its relationship to goals, expectations, standards and concerns. It is a skin disease that can have an impact on the quality of life of the sufferer. Disruption of quality of life can have a negative psychological impact and can trigger emotional symptoms such as depression, anxiety, anger, and feelings of shame that have an impact on interpersonal relationships. Several factors can cause acne such as family history or genetics, hormones, environment, emotional stress, trauma, food, medications, and cosmetics. The purpose of this study was to find out the DLQI quality of life scores before and before the intervention and the significant difference in the DLQI quality of life before and before the use of Sukma Clinic's anti-acne cream. The method used in this study is an analytical observational study and the use of a cross-sectional design by distributing the DLQI questionnaire in the form of a g-form. Samples were taken sequentially by sampling, then analyzed using the Wilcoxon test. Of the 32 respondents suffering from acne vulgaris, there were 9 (28.13%) male respondents and 23 (71.87%) female respondents. In this study, it was found that the difference in the mean DLQI quality of life score before the intervention was 8.63±8.147 to 5.78±6.210 after with p=0.006.